Secukinumab treatment of plaque psoriasis shows early improvement in DLQI response – results of a phase II regimen‐finding trial. (10th December 2015) - Augustin, M.; Abeysinghe, S.; Mallya, U.; Qureshi, A.; Roskell, N.; McBride, D.; Papavassillis, C.; Gelfand, J.
Abstract: Background: The social stigma and chronicity of psoriasis significantly affect health‐related quality of life (HRQoL). Objective: We examined the effect of three regimens of secukinumab on HRQoL in moderate to severe psoriasis patients. Methods: Twelve‐week data from a phase II, randomized, double‐blind, placebo‐controlled, regimen‐finding study evaluated HRQoL, measured by the Dermatology Life Quality Index (DLQI). Secukinumab or placebo was administered subcutaneously in three treatment regimens: single (baseline only), monthly (baseline, weeks 4, 8) and early (baseline, weeks 1, 2, 4). Differences among regimens were assessed with logistic regression models and Fisher's exact test. Results: Patients ( n = 404) were randomized to single (baseline) treatment regimen, n = 66; monthly, (baseline, weeks 4 and 8), n = 138; early, (baseline, weeks 1, 2, 4), n = 133; and placebo, n = 67. DLQI response was significantly higher in early, monthly and single regimens than in placebo regimen (40.8%, 33.6% and 13.1% vs. 1.6%, respectively; P < 0.001 for all). Conclusion: Moderate to severe psoriasis patients receiving monthly and early treatment with secukinumab demonstrated improved HRQoL compared with placebo.